PROGRAM OF COURSE OF PAINTING IN THE SYSTEM OF PREPARATION O OF STUDENTS OF THE SPECIALTY "FINE ART" - V.V. Tomashevskiy (Academy of Cognitive and Natural Sciences, 2022)
The reference program of course of painting is given in the article, in the conditions of introduction of elements of the credit-module departmental teaching, its aims and tasks are outlined, well-organized and given descriptions of the rich in content modules, prospect of further researches in this region